Inteligencia naturalista y su relación con la actitud hacia el medio ambiente en los estudiantes del 2do grado de secundaria de la I.E Wilfredo Ezequiel Ponce Chirinos - Pérez Sánchez, Mil Ton (2012)
The research aimed to determine the relationship of the naturalist intelligence to attitude toward the environment in the second grade students of secondary educational institution "Wilfredo Chirinos Ezequiel Ponce"- Yorongos. The field data was collected from 53 students through the encueta, using two data collection instruments: a naturalist intelligence scale and a scale of altitudes toward the environment. The hypothesis testing was performed by comparing the correlation coefficient with the parameters set, considering that the relationship between intelligence naturalistic attitude toward the environment is direct when the coefficient is positiva and conversely, when the coefficient is negativa. The Pearson correlation coefficient (0.89) states that there is direct relationship between the naturalist intelligence to attitude toward the environment in the second grade students of secondary educational institution 'Wilfredo Chirinos Ezequiel Ponce" - Yorongos.